2015
DOI: 10.1080/09614524.2015.1059800
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality – A challenge for development research and practice?

Abstract: Intersectionality" as a concept is increasingly finding its way into development work. In order to develop an understanding of the concept, this article shows how intersectionality can be used as a conceptual framework to analyse identity-based development claims. The article builds on qualitative research with people living in the countryside in northwest Pakistan to develop an intersectional methodology to engage with development claims. It uses a three-step analytical model to identify subject positions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Here, we note especially the lack of editorial boards that are intersectionally diverse; that is, both including females and international. Diversity is intersectional and needs to address not only gender inequality but racism, Anglocentrism, classism, ableism, and heteronormativity (Schurr and Segebart 2012;Gr€ unenfelder and Schurr 2015;Mollett and Faria 2018). The analysis in this article is therefore but an opening move for making (more) space for those bodies and lives that have been and still are excluded in geographic scholarship and for new theories, approaches, and methodologies stemming from their life worlds.…”
Section: Toward Intersectional Diversitymentioning
confidence: 99%
“…Here, we note especially the lack of editorial boards that are intersectionally diverse; that is, both including females and international. Diversity is intersectional and needs to address not only gender inequality but racism, Anglocentrism, classism, ableism, and heteronormativity (Schurr and Segebart 2012;Gr€ unenfelder and Schurr 2015;Mollett and Faria 2018). The analysis in this article is therefore but an opening move for making (more) space for those bodies and lives that have been and still are excluded in geographic scholarship and for new theories, approaches, and methodologies stemming from their life worlds.…”
Section: Toward Intersectional Diversitymentioning
confidence: 99%
“…Specifically, it explores the relationships and interactions between individual factors across multiple levels of society to determine how outcomes are shaped across societal groups (Kapilashrami and Hankivsky, 2018). Intersectional approaches are increasingly applied in development research and have been shown to improve analyses of labor market outcomes in Sub-Saharan Africa (Elu and Loubert, 2013;Grünenfelder and Schurr, 2015). From a gender perspective, it can help to tease out the interlinkages between the multiple sources of gender inequalities and "focus on the experiences of those who have been excluded thus far from feminist analysis" (Bastia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge gained can reveal entry points for enhancing youth engagement and benefits from SAI investments. The PID process revealed the need to adopt an intersectional approach that combines youth and gender analysis despite potential challenges associated with it (Grünenfelder & Schurr, 2015). We address the youth and their engagement in SAI in a separate publication.…”
Section: Discussionmentioning
confidence: 99%